Pemberian Kompres Dingin Terhadap Penurunan Nyeri Pada Asuhan Keperawatan Pasien Post Hemoroidektomi - Sari Octarina Piko; Tuti Elyta; Intan Dwi Putri (Jurnal Medika Nusantara, 2023)
Hemorrhoidectomy is a surgical removal of hemorrhoids by excision, which is removing tissue that has varicose veins (widening) that occurs in the anal canal area. This research design is analytical descriptive with case study method. The non-pharmacological implementation of post hemorrhoidectomy is the administration of cold compresses to reduce pain carried out at Bhayangkara M.Hasan Hospital, Palembang from June 15, 2022 to June 18, 2022. The subjects of this study were 2 post hemorrhoidectomy patients. Pain in Nursing Care of Post Hemorrhoidectomy Patients. The research instrument used in this study is the format of Nursing Care and Medical Records as a data collection tool. In this study, the instrument for measuring the pain scale was using the Wong Baker FACES Pain Rating Scale. As for cold compresses, the instruments used are ice packs, ice cribs, kom, perlak or blankets. Stationery and watches. After giving cold compresses for 3 days, both patients experienced a decrease in pain scale. Pain scale Mr. 'A' before giving cold compresses pain scale 4 after giving cold compresses pain scale 1. While the pain scale Mr. 'R' before giving cold compresses pain scale 5 after giving cold compresses pain scale 0. After giving cold compresses to post hemorrhoidectomy patients for 3 days, both patients experienced a decrease in pain scale.